Comparison of piezocision and discision methods in orthodontic treatment - Mustafa Cihan Yavuz; Oguzhan Sunar; Suleyman Kutalmış Buyuk; Alpdogan Kantarcı (SpringerOpen, 2018)
Abstract Background Discision method may provide an alternative to the piezocision approach in accelerated orthodontic treatment. The purpose of this study was to investigate the efficacy of discision on accelerated orthodontic tooth movement in comparison to the piezocision method in moderate crowding Angle Class I malocclusions. Methods Thirty-five female individuals were included in this clinical study. The participants were classified into three groups as conventional fixed non-extraction orthodontic treatment only (OT, n = 14), piezocision in addition to fixed non-extraction orthodontic treatment (PG, n = 9), and discision in addition to fixed non-extraction orthodontic treatment (DG, n = 12). The piezocisions and discisions were performed 1 week after placement of bonding brackets. The patients were seen at 2-3 week-intervals. Initial Little's irregularity index scores were recorded from dental casts. Periodontal parameters were measured initially, after the 1-month orthodontic treatment. Probing pocket depth, bleeding on probing, plaque index, and gingival index were recorded. Visual analog scale (VAS) was performed over the first month at different times following the bracket bonding for pain assessment. The total orthodontic treatment duration was noted. Results The duration of orthodontic treatment was statistically decreased in PG and DG compared to OT (P = 0.003). There was no statistical difference between PG and DG in orthodontic treatment duration (P > 0.05). There was no statistical difference between the two experimental groups in terms of VAS and periodontal parameter values (P > 0.05). Conclusions This is the first clinical orthodontic study to assess the effect of discision on the rate of orthodontic tooth movement. Discision is comparable to piezocision in terms of tooth movement acceleration, pain level, and periodontal status. The discision seems to be effective in reducing the time of orthodontic treatment.